Mешок, worek (Eng. ‘sack’) and others: linguo-cultural image (in Russian, Polish, and other selected European languages) - Walczak, Maciej (Papers in Linguistics, 2025)
The article focuses on the linguo-cultural specificity of a Russian and Polish lexeme мешок / worek (Eng. ‘sack’) and words that are synonymous to it. The author focuses on dictionary and language corpora data as well as on selected texts from Russian and Polish belles-lettres and idiomatic units. Regarding selected European languages, the author presents the linguistic notions typical of many languages and those that appear only in Polish and Russian. They all concern the same object of nomination, which nevertheless acquires various symbolism in the languages mentioned above. On the one hand, they connote wealth and abundance, on the other hand, they evoke poverty and never-ending expenses. Moreover, the author analyses the physical parameters of the referent (i.e. shape, size, weight, contents) and its functions (such as storage, theft, fraud, etc.), which trigger secondary metaphorical meanings.